Request and response strategies in instant messaging / Petani Mohd Noor - Petani, Mohd Noor (2016)
This study aimed to investigate two major issues: the request and response strategies towards requests for material and non-material wants demonstrated by a group of 32 Malay male speakers who resided in Japan. The data which were in Malay language and instant messaging (IM) were analyzed by using two different frameworks; (1) Fukushima’s framework (1996) was used to determine request strategies; and (2) Garcia’s framework (1993) was used to determine responses towards requests. Although Malays value indirectness in speaking as to save face of others and to maintain good relationships (Asma Abdullah, 1996), this research recorded different findings. The subjects preferred direct Head Act strategies as compared to indirectness while making requests for material and non-material wants (72.58% vs. 27.42%) which tells us that doing requests was not seen as imposition for them via online medium. Deferential and solidarious Supportive Moves were used to mitigate requests with Grounders recorded the most preferred strategy. Direct accepting responses recorded 53.48% out of the total responses which marks more than half of the requests were complied with. With no direct refusal exhibited in the data, many members chose to refuse indirectly as to save face of others or do no face threatening acts (FTA) by avoiding to respond. Therefore, it can be concluded that the subjects favored directness more than indirectness while making and responding to requests for material and non-material wants. It also suggests that solidarity is highly valued and going bald-on-record can exhibit common ground and close distant relationships between the speakers and hearers.